Using LiF Disc in Thermoluminescence Dosimetry (Baghdad Science Journal, 2008)
A LiF (TLD-700) PTFED disc has adiameter of (13mm) and thickness of (0.4mm) for study the response and sensetivity of this material for gamma and beta rays by using (TOLEDO) system from pitman company.In order to calibrate the system and studying the calibration factor. Discs were irradiated for Gamma and Beta rays and comparing with the theoretical doses. The exposure range is between 15×10-2 mGy to 1000×10-2 mGy. These doses are within the range of normal radiation field for workers.